Meningkatkan Hasil Belajar PKn Melalui Metode Jigsaw - Syamsini Syamsini (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This classroom action research departs from the background of the need for updates in teaching and learning activities conducted by both teachers and by students in particular. This study aims as an effort to increase learning outcomes students PKn through Jigsaw method with basic material central government system class IV SD Negeri 010105 Sei Silau Barat district Setia Janji academic year 2016/2017. Classroom action research was conducted in class IV of 30 students. The subjects of this study were PKn teachers and fourth grade students of SDN 010105 Sei Silau Barat, the data were collected through observation, interview, test, and study documentation. This classroom action research is conducted in 2 cycles, consisting of planning, action implementation, observation and reflection. The result of observation comparison of research in cycle I was 18.52% while cycle II was 23.97%. Keywords: jigsaw, central government Abstrak: Penelitian tindakan kelas ini berangkat dari latar belakang perlunya pembaruan dalam kegiatan belajar mengajar baik yang dilakukan oleh guru maupun oleh siswa khususnya. Penelitian ini bertujuan sebagai upaya meningkatkan hasil belajar PKn siswa melalui metode Jigsaw dengan materi pokok Sistem Pemerintahan Pusat kelas IV SD Negeri 010105 Sei Silau Barat kec. Setia Janji TP. 2016/2017. Penelitian tindakan kelas dilaksanakan dikelas IV yang berjumlah 30 orang siswa. Subjek penelitian ini adalah guru PKn dan siswa kelas IV SDN 010105 Sei Silau Barat, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Hasil perbandingan observasi penelitian pada siklus I adalah sebesar 18.52% sedangkan siklus II sebesar 23.97%. Kata kunci: jigsaw, pemerintah pusat